Catastrophe model in nonlinear dynamical systems and working groups - Butkevičiūtė, Eglė; Landauskas, Mantas; Bikulčienė, Liepa (Lietuvos matematikos rinkinys, 2015)
This paper employs catastrophe theory which analyzes changes in dynamical systems depending on two or more parameters at the same time. The main purpose of this work is to investigate the dynamics of the swallowtail catastrophe depending on the values of parameters. This catastrophe could be used as a model of leadership emergence in working groups. The best model of collected data has been found by using the particle optimization algorithm.